2014
DOI: 10.1063/1.4861432
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of n SO2 molecules (n = 1, 2, 3) with formaldehyde and thioformaldehyde

Abstract: Ab initio and density functional theory calculations are used to examine complexes formed between H2CO and H2CS with 1, 2, and 3 molecules of SO2. The nature of the interactions is probed by a variety of means, including electrostatic potentials, natural bond orbital, atoms in molecules, energy decomposition, and electron density redistribution maps. The dimers are relatively strongly bound, with interaction energies exceeding 5 kcal/mol. The structures are cyclic, containing both a O/S⋯S chalcogen bond and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 66 publications
(54 reference statements)
0
40
0
Order By: Relevance
“…Electrostatic attractions are typically supplemented by charge transfer from the lone pair(s) of one atom into the σ * or π * antibonding [29][30][31][32] orbital of the partner molecule. This same idea extends beyond chalcogen atoms, to other electronegative atoms, notably members of the halogen [33][34][35][36][37][38] and pnicogen [39][40][41][42][43][44] families, and there are very recent works that suggest that even the less electronegative C group of the periodic table can engage in very similar bonding interactions, known as "tetrel bonds."…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic attractions are typically supplemented by charge transfer from the lone pair(s) of one atom into the σ * or π * antibonding [29][30][31][32] orbital of the partner molecule. This same idea extends beyond chalcogen atoms, to other electronegative atoms, notably members of the halogen [33][34][35][36][37][38] and pnicogen [39][40][41][42][43][44] families, and there are very recent works that suggest that even the less electronegative C group of the periodic table can engage in very similar bonding interactions, known as "tetrel bonds."…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study of the heterodimer of SO 2 with H 2 CO found an equilibrium structure very much like A1 here. 38 The SÁ Á ÁO distance was longer by 0.354 Å, but R(OÁ Á ÁH) nearly the same. Consistent with the longer R(SÁ Á ÁO), the interaction energy of this dimer was 5.42 kcal mol À1 at the CCSD(T)/aug-cc-pVTZ//MP2/augcc-pVDZ level, only half that of A1.…”
Section: So 3 :H 2 Co Heterodimersmentioning
confidence: 94%
“…In the H 2 C=S···O 2 S complex, a similar distance of 3.198 Å has been predicted [33]. In contrast with the complexes between SCS and Cl − [35], OH 2 [37] or OHX(X = Cl, Br) [38], in most of the systems investigated here, the C=S···O bond is not linear.…”
Section: Structure and Interaction Energiesmentioning
confidence: 96%
“…In the complex between SO 2 and H 2 C=S, for example, a charge transfer from a SO 2 oxygen lone pair to the π*(C=S) antibonding orbital of H 2 C=S has been predicted [33]. The potential interactions of the nitrile halides XNO 2 with NH 3 as electron donor in the σ-and π-hole regions have been investigated [34].…”
Section: Introductionmentioning
confidence: 99%